Analysis of Factors Affecting Continued Interest in Using Online Food Delivery Features Using ECM and UTAUT2 - Subhan Subhan; Afan Ismi Fauzan; Yusuf Wisnu Mandaya (Universitas Negeri Semarang, 2024)
The development of e-commerce in Indonesia itself is currently at the level of being able to provide online food delivery services, making it easier for users to order food. In addition, the Covid-19 pandemic has indirectly changed consumer behavior to avoid or reduce activities outside the home, including ordering food. This study was conducted to identify what factors influence consumers in using online food delivery services with continuance intention after the pandemic and uses a method that integrates variables from the ECM (Expectancy Confirmation Model) and UTAUT2 (Extended Unified Theory of Use and Acceptance of Technology 2). The data in this study were obtained by distributing questionnaires online on 252 online food delivery users. Meanwhile, the data analysis method uses excel for the data screening process and the SmartPLS 3 application to test the inner model and outer model. The results of this study show that the most frequently used online food delivery service application is Go-Food and is dominated by women, with an age group of 17 years to 25 years, the majority of students domiciled mostly in West Java province. Then, there are six accepted hypotheses and five rejected hypotheses. Based on the accepted hypothesis, it is found that the variable price saving orientation, habit has an effect in influencing users in using online food delivery services in continuance intention. This research is expected to provide positive input for the authorities to be able to improve the quality of service provided to users in the future.